#TITLE_ALTERNATIVE# - PUSPA PANDINI (NIM : 12911040), OLGHA
This research determined the cooling water circulation system in the coastal water of Muntok, West Bangka, planned Nuclear Power Plants built. In this research conducted a simulation of hydrodynamic and thermal distribution models using MIKE 21 Flow Model FM ver. 2012 for 31 days from July 1 to July 31, 2013. The simulation results show that the tidal currents is more dominant than the currents due to wind, where at the high tide currents flowing to the south and at the low tide currents flow north. Smargorinsky Number 0.5 increase the turbulence factor, so the current speed will be slower than when using the Smargorinsky Number 0.9. When using Prandtl Number 0.5 the diffusion effect increased, the thermal distribution area (for ΔT = 0,5oC) is larger (790,455.28 m2) than when using Prandtl Number 0.9 (1,041,274.23 m2).